2016
DOI: 10.1111/bjh.14201
|View full text |Cite
|
Sign up to set email alerts
|

The tumour microenvironment influences survival and time to transformation in follicular lymphoma in the rituximab era

Abstract: The tumour microenvironment influences outcome in patients with follicular lymphoma (FL), but its impact on transformation is less studied. We investigated the prognostic significance of the tumour microenvironment on transformation and survival in FL patients treated in the rituximab era. We examined diagnostic and transformed biopsies from 52 FL patients using antibodies against CD3, CD4, CD8, CD21 (CR2), CD57 (B3GAT1), CD68, FOXP3, TIA1, PD-1 (PDCD1), PD-L1 (CD274) and PAX5. Results were compared with a sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 49 publications
3
48
0
Order By: Relevance
“…In summary, although in general agreement with previous reports (Kiyasu et al , ; Blaker et al , ; Georgiou et al , ; Menter et al , ), our data expand substantially on those studies. We show for the first time that, in DLBCL, the SP142 antibody correlates in an absolute manner with CD274/PDCD1LG2 gene amplification status assessed by FISH, but generally fails to detect low/moderate levels of the protein.…”
supporting
confidence: 94%
See 2 more Smart Citations
“…In summary, although in general agreement with previous reports (Kiyasu et al , ; Blaker et al , ; Georgiou et al , ; Menter et al , ), our data expand substantially on those studies. We show for the first time that, in DLBCL, the SP142 antibody correlates in an absolute manner with CD274/PDCD1LG2 gene amplification status assessed by FISH, but generally fails to detect low/moderate levels of the protein.…”
supporting
confidence: 94%
“…We read with interest the paper by Blaker et al (), which reported that several factors of the tumour microenvironment are associated with patient survival and time to transformation in follicular lymphoma (FL). In particular, the authors investigated the impact of PDCD1 (PD‐1)‐positive tumour infiltrating T‐lymphocytes (TILs) and CD274 (PD‐L1)‐positive macrophages in a cohort of transformed FLs using a single antibody for CD274.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Follicular lymphoma (FL) is a GC‐derived lymphoma that frequently follows an indolent clinical course . Although FL is responsive to initial chemotherapy, late relapses are common .…”
Section: Introductionmentioning
confidence: 99%
“…High infiltration of CD8+ T cells in tumor specimens is related to the inferior overall survival rate of DLBCL [13]. High degrees of intrafollicular CD68+ and programmed cell death ligand 1+ macrophage infiltration are associated with a shorter time to transformation in FL [14]. Furthermore, cancer stem cells or the tumor-initiating cells of BCL maintain their tumorigenic potential via interplay with the TME [15, 16].…”
Section: Introductionmentioning
confidence: 99%